On the Potential Energy Surface of the Pyrene Dimer - Czernek, Jiří; Brus, Jiří (International journal of molecular sciences, 2024)
Knowledge of reliable geometries and associated intermolecular interaction energy (ΔE) values at key fragments of the potential energy surface (PES) in the gas phase is indispensable for the modeling of various properties of the pyrene dimer (PYD) and other important aggregate systems of a comparatively large size (ca. 50 atoms). The performance of the domain-based local pair natural orbital (DLPNO) variant of the coupled-cluster theory with singles, doubles and perturbative triples in the complete basis set limit [CCSD(T)/CBS] method for highly accurate predictions of the ΔE at a variety of regions of the PES was established for a representative set of pi-stacked dimers, which also includes the PYD. For geometries with the distance between stacked monomers close to a value of such a distance in the ΔE minimum structure, an excellent agreement between the canonical CCSD(T)/CBS results and their DLPNO counterparts was found. This finding enabled us to accurately characterize the lowest-lying configurations of the PYD, and the physical origin of their stabilization was thoroughly analyzed. The proposed DLPNO-CCSD(T)/CBS procedure should be applied with the aim of safely locating a global minimum of the PES and firmly establishing the pertaining ΔE of even larger dimers in studies of packing motifs of organic electronic devices and other novel materials.
Keywords: molekulární modely; Thermodynamics; DLPNO; pyrene dimer; Models, Molecular; termodynamika; CCSD(T); Dimerization; potential energy surfaces; pyreny; dimerizace; intermolecular interactions; Pyrenes